Nexus Between Crop Residue Burning, Bioeconomy and Sustainable Development Goals Over North-Western India - Venkatramanan, V.; Shah, Shachi; Rai, Ashutosh Kumar; Prasad, Ram (Frontiers in Energy Research, 2021)
The crop residue burning in India particularly North-western India is responsible for air pollution episodes and public health concerns; greenhouse gases emissions and radiation imbalance; and declining soil organic matter and soil productivity. The objectives of this paper are to estimate the crop residue burning and emissions from crop residue burning, to recommend interventions in crop residue management and to propose a crop residue management-bioeconomy model incorporating strategies to sustainably manage the crop residues through interventions that enable waste valorization, food and nutritional security, farmers’ livelihood and sustainable agricultural production system. A national inventory on crop residue burning including the pollutant species was prepared using the IPCC methodology. The crop types included for the estimation are cereals, pulses, oilseeds, sugarcane, cotton, jute and Mesta. The total amount of crop residues generated and burned for the year 2017–18 was estimated at 516 million tonnes and 116 million tonnes respectively. It is estimated that 116.3 Tg of crop residues burning released about 176.1 Tg of CO2, 10 Tg of CO, 313.9 Gg of CH4, 8.14 Gg of N2O, 151.14 Gg of NH3, 813.8 Gg of NMVOC, 453.4 Gg of PM2.5, and 935.9 Gg of PM10. The emission estimates can be a proxy to prepare the national level inventory of air pollutant species from crop residue burning. The crop residue management (CRM) demands a transition from the traditional zone of CRM to bioeconomy zone of CRM, wherein the interventions aim at the sustainability of agroecosystem. The proposed bioeconomy model has a four-pronged strategy that includes smart agriculture practices, waste bioeconomy involving aspirational principles of bioeconomy, capacity building of stakeholders’ and proactive government policy. Sustainable agricultural bioeconomy provides ample opportunities to reduce crop residue burning, increase farmers’ livelihood and decarbonize the agricultural production. India’s efforts and policies can provide lessons for other agricultural regions having similar environmental constraints.